Sosioekonomisen aseman yhteydet 60-vuotiaiden liikemittarilla mitattuun liikkumisen määrään eri intensiteettitasoilla - Hokkanen, Laura-Maria (2025)
Hokkanen, L-M 2025. The associations between socioeconomic status and the amount of accelerometer-based physical activity in different intensity levels among 60-year-old adults. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis of health promotion, 66 pp., 6 appendices.